Light : a radiant history from creation to the quantum age. - Watson, Bruce (Bloomsbury, 2016)
"Delving into mythology, religion, philosophy, painting, and science, 'Light' captures the wonder and awe of humanity's study of light across three millennia of discovery"--Front jacket flap.